2017
DOI: 10.1177/0284185116684674
|View full text |Cite
|
Sign up to set email alerts
|

CT, MRI, and 18F-FDG PET/CT findings of malignant peripheral nerve sheath tumor of the head and neck

Abstract: Background Malignant peripheral nerve sheath tumor (MPNST) is a highly malignant tumor and rarely occurs in the head and neck. Purpose To describe the imaging features of MPNST of the head and neck. Material and Methods We retrospectively analyzed computed tomography (CT; n = 14), magnetic resonance imaging (MRI; n = 16), and F-FDG PET/CT (n = 5) imaging features of 18 MPNSTs of the head and neck in 17 patients. Special attention was paid to determine the nerve of origin from which the tumor might have arisen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…4B1, B2 and B3). In a recent series describing MRI features of 16 MPNST patients, Kim et al reported varying MRI features, none being specific for MPNSTs (26). Thus, in a sporadic setting, missing the pre-operative diagnosis of MPNST is common; however, most of the tumors in their series showed either moderate or marked contrast enhancement, as was seen in our case.…”
Section: Mpnstmentioning
confidence: 38%
“…4B1, B2 and B3). In a recent series describing MRI features of 16 MPNST patients, Kim et al reported varying MRI features, none being specific for MPNSTs (26). Thus, in a sporadic setting, missing the pre-operative diagnosis of MPNST is common; however, most of the tumors in their series showed either moderate or marked contrast enhancement, as was seen in our case.…”
Section: Mpnstmentioning
confidence: 38%
“…Also, invasion of adjacent structures, destruction of surrounding bone by pressure, or frank destruction is seen in 20% of cases, and it favors the diagnosis of MPNST. 21 Demeheri et al reported that the minimum apparent diffusion coefficient is lower in malignant tumors than benign MPNSTs. 24 The dynamic contrast-enhanced imaging and MR spectroscopy are additional MR sequences that can help differentiate these tumors from their benign counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Out of these, only 17 cases have been intraparenchymal lesions, while others arise from one of the nerves, either cranial or spinal. 21 22 Although the epidemiological data are very minimal, few literature reviews suggest that the average age is 39 years, with a male-to-female ratio of 1.5:1. 23 In our short series, the average age of the cohort was 34.3 years, with a male to female ratio of 0.2:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the former originates directly from brain parenchymal tissue, and it has no relationship with the cranial nerves. [13][14][15] Pathogenetically, MINSTs are supposed to originate from ectopic multipotential mesenchymal cells of the neural crest, which are displaced during embryogenesis. 16 Nevertheless, only a few cases have been reported in the literature, and lesions are commonly located in the cerebral hemispheres.…”
mentioning
confidence: 99%